Low muscle mass is associated with carotid atherosclerosis in patients with type 2 diabetes. (July 2020) - Seo, Da Hea; Lee, Yong-ho; Suh, Young Ju; Ahn, Seong Hee; Hong, Seongbin; Choi, Young Ju; Huh, Byoung Wook; Park, Seok Won; Lee, Eunjig; Kim, So Hun
Abstract: Background and aims: Sarcopenia leads to metabolic and vascular abnormalities. However, little is known regarding the independent relationship between skeletal muscle mass and atherosclerosis in patients with type 2 diabetes mellitus (T2DM). This study aimed to evaluate the association between skeletal muscle mass and carotid atherosclerosis in men and women with T2DM. Methods: In this cross-sectional study, a total of 8202 patients with T2DM were recruited from the Seoul Metabolic Syndrome cohort. Skeletal muscle mass was estimated using bioimpedance analysis, while skeletal muscle mass index (SMI, %) was defined as total skeletal muscle mass (kg)/body weight (kg) × 100. Both carotid arteries were examined by B-mode ultrasound. Carotid atherosclerosis was defined by having a carotid plaque or mean carotid intima-media thickness (IMT) ≥1.1 mm. Results: Among the entire population, 4299 (52.4%) subjects had carotid atherosclerosis. The prevalence of carotid atherosclerosis increased with decreasing SMI quartiles for both sexes. The odds ratios for carotid atherosclerosis were 2.33 (95% confidence interval [CI], 1.17–4.63) and 2.24 (95% CI, 1.06–4.741) in the lowest versus highest SMI quartile in men and women, respectively, after the adjustment for clinical risk factors. In men, the risk of atherosclerosis increased linearly with decreasing SMI quartiles ( p for trend = 0.036). Conclusions: Low skeletal muscle mass was independently associated with the presence of carotid atherosclerosis in men and women with T2DM. Graphical abstract: Image 1 Highlights: Patients with type 2 diabetes mellitus (T2DM) and carotid atherosclerosis had lower skeletal muscle mass. Low skeletal muscle mass was associated with increased risk of carotid atherosclerosis in both men and women with T2DM. The risk of atherosclerosis may be modified by skeletal muscle mass maintenance in patients with T2DM.